Measurement of η′(958) formation in two-photon collisions at LEP1 - Dova, María Teresa (1998)
The formation of the η′ in the reaction e+e−→e+e−η′→e+e−π+π−γ has been measured by the L3 detector at a centre-of-mass energy of 91 GeV. The radiative width of the η′ has been found to be <mtext>Γ</mtext>γγ<mtext>=4.17±0.10</mtext><mtext>(stat.)</mtext><mtext>±0.27</mtext><mtext>(sys.)</mtext><mspace sp="0.4" width="2px" linebreak="nobreak" is="true"></mspace><mtext>keV</mtext>. The Q2 dependence of the η′ formation cross section has been measured for <mtext>Q</mtext>2<mtext>≤10</mtext><mspace sp="0.4" width="2px" linebreak="nobreak" is="true"></mspace><mtext>GeV</mtext>2 and the η′ electromagnetic transition form factor has been determined. The form factor can be parametrised by a pole form with <mtext>Λ=0.900±0.046</mtext><mtext>(stat.)</mtext><mtext>±0.022</mtext><mtext>(sys.)</mtext><mspace sp="0.4" width="2px" linebreak="nobreak" is="true"></mspace><mtext>GeV</mtext>. It is also consistent with recent non-perturbative QCD calculations.